The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1021/acs.jpclett.9b03284
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Evolution of Surface Chemistry at the Silicon–Electrolyte Interphase via In Situ Surface-Enhanced Raman Spectroscopy

Abstract: We present a novel spectroscopic technique for in situ Raman microscopy studies of battery electrodes. By creating nanostructures on a copper mesh current collector, we were able to utilize surface-enhanced Raman spectroscopy (SERS) to monitor the evolution of the silicon anode−electrolyte interphase. The spectra show reversible Si peak intensity changes upon lithiation and delithiation. Moreover, an alkyl carboxylate species, lithium propionate, was detected as a significant SiEI component. Our experimental s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 31 publications
(52 reference statements)
1
19
0
Order By: Relevance
“…[162] Furthermore, in situ Raman spectroscopy was used to investigate the evolution of SEI on nanocrystalline Si in lithium-ion batteries. [373] It was demonstrated that reversible Si peak intensity changed upon lithiation and delithiation, and alkyl carboxylate species (lithium propionate) were one representative of the SEI components. Meanwhile, Nanda et al first employed tip-enhanced Raman spectroscopy to observe nanoscale chemical and topographical heterogeneity of a SEI formed on amorphous Si at different cycle numbers.…”
Section: Advanced In Situ/operando Characterizations On Silicon-basedmentioning
confidence: 99%
“…[162] Furthermore, in situ Raman spectroscopy was used to investigate the evolution of SEI on nanocrystalline Si in lithium-ion batteries. [373] It was demonstrated that reversible Si peak intensity changed upon lithiation and delithiation, and alkyl carboxylate species (lithium propionate) were one representative of the SEI components. Meanwhile, Nanda et al first employed tip-enhanced Raman spectroscopy to observe nanoscale chemical and topographical heterogeneity of a SEI formed on amorphous Si at different cycle numbers.…”
Section: Advanced In Situ/operando Characterizations On Silicon-basedmentioning
confidence: 99%
“…To circumvent this limitation, Raman signal enhancement techniques using the plasmon resonance properties of metal nanostructures were successfully implemented to extract compositions of surface films developed on various electrode materials upon contact with organic carbonate electrolytes. Surface-enhanced Raman spectroscopy (SERS) has been carried out operando on SERS-active silver and gold nanostructured electrodes starting from 2000. More recently, tip-enhanced Raman spectroscopy (TERS) using silver or gold scanning nanoprobes demonstrated the ex situ mapping of the SEI composition distribution with nanoscale resolution on a non-SERS active electrode material (silicon anode) in a similar way as nanoinfrared mapping was achieved on tin anodes a few years before . TERS, despite recent significant advances since its demonstration under operando conditions, , has not been yet implemented in a LIB electrolyte because of the difficulty to control the atmosphere and prevent the electrolyte evaporation in open cells.…”
mentioning
confidence: 99%
“…Finally, the surface enhanced Raman scattering (SERS) technique must be mentioned. With SERS the Raman spectra from the electrode/electrolyte interface can be significantly enhanced and in situ experiments can be performed, [40,41] however, there is a need to decorate the surface with nanoparticles based on metals such as Ag and Au or to nanostructure the surface of the sample. The former approach has an implicit problem of alloying the metal particles with lithium and the latter one creates an implicit risk of influencing the mechanism and/or the kinetics of the reactions under study.…”
Section: Raman Microspectroscopy For Batteriesmentioning
confidence: 99%